THE PROBLEM OF FOUNDATION OF THE CULTURE OF YOUTH HEALTH IN PEDAGOGICAL THEORY - Bashtan, Svitlana; Shapkina, Tatyana (Educological discourse, 2019)
Nowadays the issue of health is very topical as the increase of material and technical base of the society positively influences the well-being of the population, however, at the same time, the youth do not vividly realize the limits of the allowed choices of way of life, moral ideals and leisure. Elevation of the motivation for healthy way of life among youth should be provided through the formation in the society and in every individual an appropriate mechanism of health care culture. The article deals with the problems of forming the health culture of students in pedagogical theory. Special attention has been paid to the problem of health in modern researches. The subject of scientific researches is determined by the scholars as the specification of ways of forming the health culture of teachers. However the development of educational and methodical tools for the formation of health protection culture of the high school students needs additional experimental researches. The preconditions and conditions for forming the foundations of the culture of youth health are determined. We analyse reasons according to which the process of forming a culture of health of students can be considered as a pedagogical problem. The sequence and structure of solving the pedagogical problem of formation of the bases of the culture of health of student youth are determined. The analysis of the research literature allowed to distinguish supporting two concepts: "culture" and "health" and the accompanying concept of "healthy lifestyle". Theoretical understanding of the problem made it possible to determine the nature and content of the health culture in general and for students. Based on the generalized results of theoretical analysis culture of health as an integral part of human culture, the formation of knowledge, abilities and skills which raise healthy individual livelihoods.